2012
DOI: 10.1093/wber/lhs010
|View full text |Cite
|
Sign up to set email alerts
|

Antidumping, Retaliation Threats, and Export Prices

Abstract: Utilizing four-dimensional (firm-product-destination-year) Brazilian firm-level export data, we show that antidumping (AD) duties result in a significant and dramatic increase in the unit values of the products that firms export to duty-imposing countries. Furthermore, we examine the effect of potential (retaliatory) AD duties on the unit price of the firms' shipments. Our findings suggest that AD activities in Brazil lead Brazilian exporting firms to increase their unit export prices for the named industries'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…56 Meckling and Hughes (2017) further suggest that transnational corporations operating in the solar photovoltaic industry may prefer open trade due to fears or threats of retaliation along other product lines, which could damage economic profits (232). Avsar (2013) similarly found that AD activities in Brazil lead Brazilian exporting firms to increase export prices for the products of named industries to decrease dumping margins and avoid threats of retaliatory measures by other countries. There is reason to believe, therefore, that firms include the possibility of retaliatory antidumping measures within their strategic calculus.…”
Section: Antidumping: Why?mentioning
confidence: 99%
“…56 Meckling and Hughes (2017) further suggest that transnational corporations operating in the solar photovoltaic industry may prefer open trade due to fears or threats of retaliation along other product lines, which could damage economic profits (232). Avsar (2013) similarly found that AD activities in Brazil lead Brazilian exporting firms to increase export prices for the products of named industries to decrease dumping margins and avoid threats of retaliatory measures by other countries. There is reason to believe, therefore, that firms include the possibility of retaliatory antidumping measures within their strategic calculus.…”
Section: Antidumping: Why?mentioning
confidence: 99%
“…One body of research studies the impact of antidumping on global trade. Within this research, scholars have documented the trade and price impacts of antidumping (including, but not limited to Krupp, 1994; Prusa, 1997; Prusa, 2001; Brenton, 2001; Bown & Crowley, 2007; Ganguli, 2008; Vandenbussche & Zanardi, 2010; Avsar, 2013; Besedeš & Prusa, 2017). This set of papers suggests that antidumping duties increase import prices, and they have a dramatic impact on trade flows not only from target countries but also from third countries not named in the investigations.…”
Section: Related Literature and Contributionmentioning
confidence: 99%
“…Konings and Vandenbussche (2013) estimate the impact of antidumping on export behavior of French firms protected by antidumping and finds that while non‐exporting firms benefit from protection, domestic sales of export‐oriented firms decrease because of antidumping. Using Brazilian firm‐level data, Avsar (2013) shows that even the threat of antidumping in the export markets increases the prices of shipments. Chandra (2019) demonstrates that U.S. antidumping duties lead the Indian exporters to alter their product‐scope to markets other than the United States.…”
Section: Related Literature and Contributionmentioning
confidence: 99%
See 1 more Smart Citation